Subclinical Changes in Deceased Donor Kidney Proteomes Are Associated With 12-month Allograft Function Posttransplantation—A Preliminary Study. Issue 2 (February 2019) - Kaisar, Maria; van Dullemen, Leon; Charles, Philip; Akhtar, Zeeshan M.; Thézénas, Marie L.; Huang, Honglei; Klooster, Astrid; Watkins, Nicholas A.; Kessler, Benedikt; Ploeg, Rutger J.
Abstract : Background: Cerebral injury during donation after brain death may induce systemic damage affecting long-term kidney function posttransplantation. Conventional evaluation of donor organ quality as a triage for transplantation is of limited utility. Methods: We compared donor kidneys yielding opposing extremes of the continuum of posttransplantation outcomes by several common kidney biopsy evaluation techniques, including Kidney Donor Profile Index and Remuzzi scoring, and analyzed tissue from a minimal sample cohort using label-free quantitation mass spectrometry. Further assessment of the proteomic results was performed by orthogonal quantitative comparisons of selected key proteins by immunoblotting. Results: We show that common evaluation techniques of kidney biopsies were not predictive for posttransplantation outcomes. In contrast, despite the limited cohort size, the proteomic analysis was able to clearly differentiate between kidneys yielding extreme posttransplantation outcome differences. Pathway analysis of the proteomic data suggested that outcome-related variance in protein abundance associated with profibrotic, apoptosis, and antioxidant proteins. Immunoblotting confirmation further supported this observation. Conclusions: We present preliminary data indicating that there is scope for existing evaluation approaches to be supplemented by the analysis of proteomic differences. Furthermore, the observed outcome-related variance in a limited cohort was supported by immunoblotting and is consistent with mechanisms previously implicated in the development of injury and cytoprotection in kidney transplantation. Abstract : Proteomic analyses using mass spectrometry and immunoblot of a small cohort of kidneys from brain death donors is superior to predict graft function (estimated glomerular filtration rate at 3 and 12 months) versus clinical and histological standard classifications. Supplemental digital content is available in the text.